2019
DOI: 10.1089/pop.2018.0048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Care and Socioeconomic Needs on Health Care Utilization and Disease Management: The University of New Mexico Hospital Care One Program

Abstract: Understanding how unmet basic needs impact health care in patients with complex conditions is vital to improve health outcomes and reduce health care costs. The purpose of this observational study was to explore the association between health care and socioeconomic needs and health care utilization and disease management among patients with chronic conditions at an intensive, patient-centered, office-based program. The study used a cross-sectional design and a convenience sampling approach. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Evidence has shown that unmet HRSNs contribute to poor health outcomes through increased exposure to risk factors for chronic conditions, higher likelihood of chronic stress, and decreased access to resources for those with preexisting conditions [3]. Patients with HRSNs also have higher emergency department utilization [4][5][6], higher hospital admissions [7,8], higher rates of hospital readmission [9], and higher rates of missed ambulatory appointments [10,11], which coincide with higher cost to the health system [12]. Recent interventions integrating social care in clinical settings have demonstrated improvements in health outcomes and cost by addressing food security [13], housing stability [14,15], and legal assistance [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that unmet HRSNs contribute to poor health outcomes through increased exposure to risk factors for chronic conditions, higher likelihood of chronic stress, and decreased access to resources for those with preexisting conditions [3]. Patients with HRSNs also have higher emergency department utilization [4][5][6], higher hospital admissions [7,8], higher rates of hospital readmission [9], and higher rates of missed ambulatory appointments [10,11], which coincide with higher cost to the health system [12]. Recent interventions integrating social care in clinical settings have demonstrated improvements in health outcomes and cost by addressing food security [13], housing stability [14,15], and legal assistance [16,17].…”
Section: Introductionmentioning
confidence: 99%